2024
DOI: 10.1680/jbren.21.00063
|View full text |Cite
|
Sign up to set email alerts
|

Application of deep learning in structural health management of concrete structures

Abstract: Structural health management constitutes an essential factor in ensuring the durability of concrete structures. Cracks in concrete, reinforcement corrosion, alkali-silica reaction, and efflorescence attacks are commonly concrete defects that can be identified visually. However, detection and classification of these defects in concrete bridges and other high-rise concrete structures are difficult and expensive process in manual approaches. In this research, a deep learning application is applied to detect and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The obtained computation results showed that there is statistical significance between the variables at a 95% confidence interval with a P value of 0.047, 0.023 and 0.013 for compressive, flexural, and splitting tensile strength respectively which is less than the critical value of 0.05. This analysis offers valuable insights for optimizing mix designs and enhancing the overall performance and durability of laterized concrete in various construction applications 82 .…”
Section: Results Discussion and Analysismentioning
confidence: 99%
“…The obtained computation results showed that there is statistical significance between the variables at a 95% confidence interval with a P value of 0.047, 0.023 and 0.013 for compressive, flexural, and splitting tensile strength respectively which is less than the critical value of 0.05. This analysis offers valuable insights for optimizing mix designs and enhancing the overall performance and durability of laterized concrete in various construction applications 82 .…”
Section: Results Discussion and Analysismentioning
confidence: 99%
“…The design of experiments constitutes a systematic assessment of the factor levels or component variable effects of the mixture in a simultaneous manner on the target response function, which is achieved using response surface methodology [ 36 ]. The deployment of this essential tool in laboratory experiments research helps to yield the minimization of cost and time resources by the generation of a maximum quantity of information for limited laboratory test trials.…”
Section: Materials and Methodologymentioning
confidence: 99%
“…Multi-class classification has also been used to classify cracks based on their characteristics. Uwanuakwa et al [21] used DL to classify the type/cause of cracks as vertical, diagonal, shrinkage, efflorescence, alkali-silica reaction or corrosion cracks; And Gao and Mosalam [22] used multi-class classification to classify the level and type of damage in concrete structures.…”
Section: Introductionmentioning
confidence: 99%